2000
DOI: 10.1001/archinte.160.16.2537
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Urine Culture

Abstract: Background: Dysuria is one of the most common presenting complaints of young women, and urinalysis is one of the most common laboratory tests performed. Despite the fact that the midstream clean-catch technique is commonly used for urine collection, contaminated urine cultures occur with distressing regularity. The midstream clean-catch technique is time-consuming to explain, frequently not performed correctly by patients, costly for supplies, often embarrassing for patients and staff, and of unproven benefit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(25 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…The difficulties in getting a genuine “clean-catch” MSU sample representative of only organisms originating from the bladder is well-recognized and especially so for females, in which the urine has to pass through the distal urethra and/or for the elderly (both male and female), who have physical or other impairments (Franz and Hörl, 1999; Lifshitz and Kramer, 2000; Wilson and Gaido, 2004). Nonetheless, it is less intrusive than alternative approaches, such as bladder tissue biopsy or catheterization, and hence the most pragmatic and ethical approach for larger, longitudinal studies and clinical application and it was therefore our positive intention to collect samples in this way (Wolfe et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The difficulties in getting a genuine “clean-catch” MSU sample representative of only organisms originating from the bladder is well-recognized and especially so for females, in which the urine has to pass through the distal urethra and/or for the elderly (both male and female), who have physical or other impairments (Franz and Hörl, 1999; Lifshitz and Kramer, 2000; Wilson and Gaido, 2004). Nonetheless, it is less intrusive than alternative approaches, such as bladder tissue biopsy or catheterization, and hence the most pragmatic and ethical approach for larger, longitudinal studies and clinical application and it was therefore our positive intention to collect samples in this way (Wolfe et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…If a clean-catch urine specimen is challenging for a patient to obtain (eg, obesity, arthritis), a simple voided specimen, although less ideal, can be used. 39 …”
Section: The Evidence: Diagnosis Management and Preventionmentioning
confidence: 99%
“…While no significant differences were observed between first-void and midstream urine in males, there are significant variations in female first-void urine compared with midstream urine, probably due to bacterial contamination (Schaub et al, 2004). Other studies showed that approximately 40% of bacterial contamination in female urine samples derived from the skin contamination (Finkel, 2006;Lifshitz and Kramer, 2000). However, by using a prostatic fluid indicative panel, Theodorescu et al (2008) discovered a panel of 12 novel prostate cancer (PCa) biomarkers in the first-void urine, in addition to collection of sufficient amounts of prostatic fluid.…”
Section: Sample Collection: First-void or Midstream Urine?mentioning
confidence: 89%